INTEGRATING SUNDANESE ETHNOMATHEMATICS INTO MATHEMATICS CURRICULUM AND TEACHING: A SYSTEMATIC REVIEW FROM 2013 TO 2020 - Dindin Abdul Muiz Lidinillah; Rahman Rahman; Wahyudin Wahyudin; Sani Aryanto (Jurnal Infinity, 2022)
As a country with the most ethnic, cultural, and linguistic backgrounds globally, Indonesia has great potential for the development of ethnomathematics studies. Among those ethnic groups, Sundanese ethnic group and culture is the second-largest after the Javanese ethnic group and culture, making it interesting to study because it has rich cultural elements that can be integrated into the mathematics curriculum in schools. This article explores the development of research on ethnomathematics based on Sundanese culture, including those which are based on the study's scope, the integration of Sundanese ethnomathematics into the school curriculum, and mathematics learning. Based on the investigation, there has been no systematic literature review on Sundanese ethnomatematics. The research was conducted using the Systematic Literature Review method with the PRISMA protocol. The results showed that there were various kinds of research on Sundanese ethnomathematics. There were various kinds of study on Sundanese ethnomathematics integration into mathematics curriculum and teaching using five model categories. The results also showed that RME, CTL and PBL were the most widely used teaching approaches for learning Sundanese ethnomathematics. However, most of Sundanese ethnomathematics teaching uses a special approach Â that varies, developing teaching material, teaching media and using the context of traditional games.